The Influence of Digital Payment Systems on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Lalabata District, Soppeng Regency - Sukma Aini; Mutmainna Andi Sudirman (GENTARA: management and accounting research, 2026)
The background of this research problem is to determine the influence of Digital Payment Systems on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Lalabata District, Soppeng Regency.This research is classified as quantitative. The data sources are secondary data. The data analysis method used is multiple linear regression. Furthermore, the hypothesis was tested using the F-test, t-test, and coefficient of determination. The results of this study indicate that digital payment systems affect the performance of MSMEs in Lalabata District, Soppeng Regency